PENINGKATAN KINERJA USAHA MELALUI ANALISIS NET PROFIT MARGIN(NPM) - Moch Aminnudin; Hamdi Sari Maryoni (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aims to determine the increase in business performance through the analysis of Net Profit Margin (NPM) in Siti Snack's business. The research method used is a research method with quantitative analysis which tries to show the measurement of financial performance through NPM ratio analysis. The data used are secondary data originating from the financial statements of Siti Snack's business as the research sample for 2019. Based on the results of research and analysis of the financial performance assessment data of the